Are humans really that bad at theory-based judgments? The effect of evolutionary relevance of the content - Hromatko, Ivana (Array, 2011)
Humans constantly have to detect covariations among many events, especially the ones in their social surrounding. Imperfections of this process led some authors to argue that an “intuitive scientist” is not capable of precise assessment of covariations. Here we argue that the tasks used in previous studies contained information that could not have been relevant during our evolutionary past, and thus no functional heuristics could have evolved to successfully solve this kind of problems. To test this assumption we compared the accuracy of two kinds of theory-based judgments: in terms of our evolutionary past, one set of tasks contained relevant and the other irrelevant information. The participants were significantly more precise (but not faster) at judging the covariations between the “evolutionary relevant” variables. It seems that “intuitive scientist” can make a rather fair estimate of covariatons in nature, but only when the failure to do so might result in decreased chances of survival and/or reproduction.